Success factors in university–industry PhD projects. (18th February 2016) - Salimi, Negin; Bekkers, Rudi; Frenken, Koen
Abstract: Faced with ever-increasing pressure to innovate, firms consider universities to be significant sources of knowledge. Such knowledge flow can take place in a variety of ways such as academic publications and contract research, but also in more collaborative modes such as joint research projects. This paper focuses on a specific collaborative model, in which firms and universities are involved together in a PhD project. We analyze the effects of project management, communication, and supervision characteristics on the success of such PhD projects using a survey conducted at Eindhoven University of Technology, the Netherlands. We conclude that management decisions, supervision and communication characteristics have a significant impact on the ultimate success of a project. Among other things, the choice of university supervisor plays a pivotal role. Success is more likely if there is joint decision-making by both university and partner. We believe our findings help universities and firms to collaborate successfully.